Accounting education from 1960 to 2023: a bibliometric review - Hu, Guojing; Muhamad, Haslinah; Mustafa, Hasri; Alhasnawi, Mushtaq Yousif (International Journal of Evaluation and Research in Education (IJERE), 2025)
Since 1960, publications in accounting education have demonstrated a high level of productivity and influence. However, few studies have attempted to use bibliometric methods to map and visualize accounting education research. This study aimed to identify global issues in accounting education through bibliometric analysis, covering the period from 1960 to 2023, by exploring publication trends, top topics, and major contributors in the field. Tools such as Microsoft Excel, VOSviewer, the bibliometric R-package, and WordSift were utilized to comprehensively analyze 717 Scopus-indexed documents. The findings underscore a continuous and recently accelerated historical evolution of accounting education publications, with primary research areas clustering around “business, management, and accounting.” Noteworthy trends include a geographic concentration in the United States, the United Kingdom, and Australia, with RMIT University emerging as a key contributor. Hassell, from the United States, is recognized as the most influential author, and “accounting education” from Taylor & Francis stands out as the most productive journal. Works by Bui and Porter in 2020 emerge as the most frequently cited documents. The research results indicate that future research directions should focus on students, higher education, and the profession, emphasizing themes such as curriculum, learning, and skills.